Generation of field-reversed configurations via neutral beam injection - T. Roche; S. Dettrick; A. Fontanilla; S. Gupta; M. Onofri; J. A. Romero; L. C. Steinhauer; M. T. Tobin; E. M. Granstedt; L. Galeotti; S. Karbashewski; R. M. Magee; et al. (Nature Communications)
Abstract We report evidence of successful generation of field-reversed configuration plasmas by neutral beam injection. This is achieved by trapping the steady-state beams in an initial seed plasma, hence providing a direct source of toroidally directed energetic ion current and increase plasma density and temperature until plasma and magnetic pressures become comparable. Magnetic flux trapping occurs gradually, and the change in topology from open field line to fully a formed field-reversed configuration is complete within  ~ 10 ms. Field reversal is first established using a traditional metric and complemented by advanced reconstruction algorithms of the magnetic topology and plasma pressure profiles; observations of characteristic changes to fast-ion orbits inferred from magnetic fluctuations; and an experimentally validated model of field reversal by neutral beam injection. These results establish a field-reversed configuration formation method which may offer technological and economic advantages on a path to a future fusion energy system.